STRUKTUR PRODUKSI GETAH, PERTUMBUHAN DAN KAJIAN FENOTIPIK KEMENYAN (Styrax sp) - Agung Wibowo; Arida Susilowati; Kansih Sri Hartini (Peronema Forestry Science Journal, 2016)
Kemenyan tree was North Sumatera local species that produce high valuable resin and prospective export comodities. Recently, information about kemenyan resin production, growth structure and phenotypic studies still not determined yet. The objectives of this research were : (1) To determine resin production baseline data, growth structure and growth character related with resin production for further characterization research and (2). To estimate genetic variable of resin production through phenotypic characterization. SPSS and Minitab software were used for determined some variable of research. The result showed that kemenyan stand on Banuaji IV Village has resin production average as much 192,6 g/tree/yield and right-skewness resin production distribution structure. Pearson correlation test and multiple linear regression for 11 growth characters showed 9 characters that correlated with resin production (r: 0.18-0,734) and regression test showed that bark thickness and stem diameter character can be used as indicator for high resin tree selection. The result on phenotypic study showed that resin production character has high narrow sense heritability (h2: 0.55 – 0.60). It indicated that resin production character dominanly influenced by genetic factor. Keywords: kemenyan, resin, production, phenotypic, heritability